Duplikasi watak dan pergerakan wayang gedek ke animasi - Aminah, Abd Karim (Universiti Malaysia Sarawak (UNIMAS), 2013)
The process of creating animation starts from the development of idea to sketches and followed by the process of animating the character. However, there is a lack of research in the aspect movement and character duplication from an existing media into animation. The main purpose of this study is to answer the research question 'how is the process of duplicating characters and movement from an existing media into animation' by using wayang gedek as the subject matter.